Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/j.pain.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a central mode of action for etoricoxib (COX-2 inhibitor) in patients with painful knee osteoarthritis

Abstract: The COX-2 inhibitor etoricoxib modulates the peripheral and central nociceptive mechanisms in animals. This interaction has not been studied in patients with pain. This randomized, double-blind, placebo-controlled, 2-way crossover, 4-week treatment study investigated the pain mechanisms modulated by etoricoxib in patients with painful knee osteoarthritis. Patients were randomized to group A (60 mg/d etoricoxib followed by placebo) or B (placebo followed by 60 mg/d etoricoxib). The quantitative, mechanistic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 76 publications
2
66
0
13
Order By: Relevance
“…These findings are similar to those in humans. Both Graven-Nielsen et al 15 and Arendt-Nielsen et al 16 showed human OA patients have less efficient CPM compared with healthy controls as assessed using an MQST stimulus 3,6 . In contrast, in humans, the use of TQST to assess CPM has not produced such consistent results.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are similar to those in humans. Both Graven-Nielsen et al 15 and Arendt-Nielsen et al 16 showed human OA patients have less efficient CPM compared with healthy controls as assessed using an MQST stimulus 3,6 . In contrast, in humans, the use of TQST to assess CPM has not produced such consistent results.…”
Section: Discussionmentioning
confidence: 98%
“…В 2016 г. были опубликованы результаты рандомизи-рованного исследования среди пациентов с остеоартро-зом, подтверждающего модулирующее влияние этори-коксиба не только на механизмы периферической сенси-тизации (повышение порога восприятия боли), но и на центральную сенситизацию на уровне нейронов задних рогов спинного мозга (уменьшение временной суммации болевого импульса и уменьшение зон вторичной гипе-ралгезии). Эторикоксиб в данном исследовании принима-ли в течение 4 недель в дозе 60 мг [11].…”
Section: лечение острой неспецифической боли в спинеunclassified
“…В то же время отдельные фармакокине-тические исследования демонстрируют способность высокоселективного НПВП -эторикоксиба проникать через гематоэнцефалический барьер в концентрациях, достаточных для подавления ЦОГ-2 [18]. В 2016 г. опубликованы результаты одного из первых клинических исследований влияния эторикоксиба на центральные механизмы возникновения и поддержания боли [19]. В ходе этого рандомизированного двойного слепого плацебо-контролируемого двустороннего пере-крестного исследования изучали механизм действия эторикоксиба у пациентов с болевым остеоартритом коленного сустава посредством оценки клинических параметров боли, оценки периферической и централь-ной сенситизации с использованием экспериментальных, механистических биомаркеров боли.…”
Section: общие принципы неинвазивной терапии хронической боли в спинеunclassified